Applications for data collection: AppDatCol - Pandey, Anuj; ., Surachna; Mishra, Sidharth Sekhar (International Journal Of Community Medicine And Public Health, 2021)
Health surveillance or routine health surveys are the main sources of health-related information in developing countries. The need to support the paper process and the recent advanced popularity of mobile devices fortified the development and use of electronic data collection methods in community health and clinical research works. Data collection apps are mobile applications that make it possible to collect data from a smartphone, tablet, or iPad. The main objective of this article is to explore different type of applications easily available for using as a tool for data collection purpose. This article will brief about software’s that are easily available to be customized and can be used for data collection. Mobile data collection apps are becoming integral to secure, reliable, and scalable research. The efficiency and dependability of these mobile survey apps, even in offline settings, open doors to new research possibilities. It begins with the freedom and adaptability of designing research-specific forms that work even in the most challenging environments. Sharing experiences of the barriers and distinct benefits of this technology will help future users to be better informed and allow for the swifter adoption of these and similar technologies. Although any digital form may suffice for the purpose of data gathering, not every data collection system may be used for sensitive, clinical or research data. We believe that Teamscope and CSPro stands out in the mobile data collection landscape and is the best choice for research purposes. No other application combines data encryption, passcode lock, cross-device compatibility with iOS and android, support for both cross sectional and longitudinal studies, like these applications does.